Natural resources, corruption, human development, economic growth, prices of minerals and fiscal fluctuations - Urbina Padilla, Dante Abelardo (2021)
This thesis analyzes issues related to natural resources, corruption, human development, economic growth, prices of minerals and fiscal fluctuations. It is composed of two studies. The first one analyzes the effects of corruption on economic growth, human development and natural resources in Latin American and Nordic countries using a Bayesian panel VAR model. The results reveal some relevant contrasts between both groups of countries: (i) in Latin America there is support for the sand the wheels hypothesis in Bolivia and Chile, support for the grease the wheels hypothesis in Colombia and no significant impact of corruption on growth in Brazil and Peru. By contrast, the response of growth to shocks in corruption is significantly negative in most of periods in all Nordic countries; (ii) corruption negatively affects human development in all countries from both regions; (iii) corruption tends to spur natural resources sector in Latin American countries, especially in Brazil, Colombia and Peru. By contrast, corruption is detrimental for the activity of natural resources sector in all Nordic countries. Furthermore, results for the full sample, Latin American and Nordic countries are obtained from two alternative approaches, namely, a Panel Error Correction VAR model and an Asymmetric Panel VAR model. The second study analyzes the evolution of the effects of fluctuations in mineral commodity prices on fiscal variables, especially those associated with fiscal revenues, in Peru by means of VAR models with time-varying parameters and stochastic volatility (TVP-VAR-SV). Different alternative specifications are compared using the marginal likelihood and the deviance information criterion. It is found that an increase of 1% in the growth of mineral commodity prices generates increases of around 1.5% and 2.5% in the growth of taxes from mining and mining canon, respectively, thus reflecting a remarkable sensitivity of these variables to external shocks. In turn, these responses are increasingly more pronounced until reaching a peak around 2009 and then decrease, which is in line with the dynamics of the commodities boom. In the variance decomposition, the importance of shocks in mineral commodity prices in explaining fluctuations in taxes from mining and mining canon increases in line with the increasing tendency of mineral prices until the Great Recession, where shocks in mineral commodity prices explain between 40% and 50% of fluctuations in taxes from mining and mining canon, and then it is reduced. This shows the importance of allowing time-varying parameters and stochastic volatility in contrast with a standard VAR.